Photovoltaic properties of semiconductor (ZnSe)/polymer (PEO-Chitosan blend) junction for solar cells applications - Mohamad, Souad A.; Ali, Moazzam H.; Ibrahim, Zainol Abidin; Arof, Abdul Kariem (Trans Tech Publications, 2006)
The properties of ZnSe/PEO junction photoelectrochemical cells have been studied under dark and illuminated conditions. ZnSe was electrodeposited onto an indium tin oxide (ITO) glass and the polymer film of PEO-chitosan: NH4I (+I2) was placed over it followed by another ITO glass. The polymer film was prepared by the solution cast technique. The open circuit voltage (Voc) of the fabricated cells was between 300 mV to 400 mV. In the dark the device operates as a diode while under illumination it operates as a photoelectrochemical cell.